Islamic-Based Community Empowerment: Building Family and Women’s Resilience at Jogokaryan Mosque - Syafril Wicaksono; M Khoirul Hadi al Asy Ari; Muktazzah Fiddini (Tunas Institute, 2025)
This study examines family, women, and children’s resilience based on mosque empowerment, focusing on the Jogokaryan Mosque’s Ramadhan Culinary Village in Yogyakarta. The research aims to explore how mosque-based community programs strengthen family structures and enhance women’s and children’s resilience through religious and social activities. Using a qualitative content analysis approach, this library research investigates three main questions: (1) how the Jogokaryan Mosque designs its empowerment model; (2) what role mosque empowerment plays in developing family, women, and children’s resilience; and (3) how the Ramadhan Culinary Village functions as a form of mosque-based empowerment. The findings reveal that the Jogokaryan Mosque applies an integrated empowerment model rooted in Islamic values, combining religious guidance, economic activities, and community engagement. This approach fosters economic independence, strengthens family relationships, and increases women’s participation in community development while nurturing children’s moral and social resilience. The Ramadhan Culinary Village serves not only as an economic hub but also as a means of social and spiritual reinforcement for the surrounding community. Thus, mosque empowerment at Jogokaryan demonstrates how Islamic institutions can function as centers for holistic resilience-building spiritually, socially, and economically within the framework of Islamic community development.